Histomorphological Study of Nephrectomy Specimens in a Tertiary Care Hospital Of Chattogram: An Observational Study - Nasreen, Sayeeda; Sadaf, Anika; Ahamad, Shahab Uddin; Rahman, Md Zillur (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Now a-days nephrectomy is not an uncommon surgery practiced in urology. Not only the clinical suspicions are confirmed but also many unsuspecting lesions are brought to light by the histopahological study.Elective nephrectomy is done for both benign and malignant diseases of the kidney. On the other hand, trauma is the most common cause of emergency nephrectomy. To observe the demographic and histopathological aspects of nephrectomy specimens in a tertiary care hospital of Chattogram: Chittagong Medical College Hospital. Materials and methods: This was an observational study of nephrectomy specimens received in the Department of pathology, Chittagong Medical College over a period of one year (January to December 2019). The studied parameters were: frequency, age, sex, laterality, clinical presentation, histological type and morphologic characteristics. Results: There were 30 nephrectomy specimens of which 09 were non-neoplastic and 21 were neoplastic lesions. Among the neoplastic lesions, all the cases were malignant with no significant side and sex differences of patients. The most frequent (26.67%) age rage was 0-10 year and renal cell carcinoma was the commonest (13 out of 21 cases, 61.90%) malignant tumor. Among the nonneoplastic lesions, chronic pyelonephritis was the most frequent benign lesion (5 out of 9 cases, 55.56%). Conclusion: In this study, there was a much higher rate of nephrectomy performed for malignant conditions of the kidney compared to other developing countries, where benign lesions are the main cause of nephrectomies. JCMCTA 2020 ; 31 (1) : 58-63